Relay-Aided Uplink NOMA Under Non-Orthogonal CCI and Imperfect SIC in 6G Networks - Volkan Ozduran; Nikolaos Nomikos; Ehsan Soleimani-Nasab; Imran Shafique Ansari; Panagiotis Trakadas (IEEE Open Journal of Vehicular Technology)
Sixth generation (6G) networks must guarantee radio-resource availability for coexisting users and machines. Here, non-orthogonal multiple access (NOMA) can address resource limitations by serving multiple devices on the same spectral and temporal resources. Meanwhile, cooperative relays can mitigate the impact with excessive large- and small-scale fading and interference. Still, to unlock the full potential of NOMA in 6G deployments, its performance must be analyzed under interference-limited scenarios with NOMA communications occuring across multiple cells. In this paper, the detrimental effect of co-channel interference (CCI) from nearby NOMA transmissions on a relay-aided NOMA network is examined. More specifically, randomly deployed CCI terminals communicate using NOMA and degrade the uplink communication. Network performance is thoroughly analyzed for various metrics, considering independent and identically distributed non-orthogonal CCI. Furthermore, for improved performance, transmit power, power allocation, and relay location optimization is presented. This scenario can correspond to Industry 4.0 settings, relying on private networks that can adjust the transmit power of interferers within the network. Our analytical findings are verified through Monte-Carlo simulations, revealing that non-orthogonal CCI degrades the system performance, causing system coding gain losses. Nonetheless, the proposed optimization framework can mitigate the impact of non-orthogonal CCI and ensure improved uplink performance.